Training Teachers in China to Use the Philosophy for Children Approach and Its Impact on Critical Thinking Skills: A Pilot Study - Caiwei Wu (Education Sciences, 2021)
Philosophy for Children (P4C) is an educational approach that helps children question, reason, construct arguments, and collaborate with others. This approach to teaching is new to Chinese teachers and students who have traditionally relied on rote learning and dissemination of knowledge. Independent thinking and questioning are rarely encouraged. This article reports on a pilot study aimed at training teachers in one school in mainland China to use P4C to promote thinking skills. Six year 7 classes (age 12–13) and their teachers were randomly assigned to receive P4C training (n = 90 pupils) or to a control group (n = 88). The intervention ran for 4 weeks. The study found that teachers appreciated the P4C methods but were concerned about using the method in their regular curriculum. An impact evaluation shows that students who were taught P4C experienced a small improvement in thinking skills, measured using a composite of validated critical thinking tests.